2021
DOI: 10.3390/ijerph182010997
|View full text |Cite
|
Sign up to set email alerts
|

Adult-Attention Deficit Hyperactive Disorder Symptoms Seem Not to Influence the Outcome of an Enhanced Agonist Opioid Treatment: A 30-Year Follow-Up

Abstract: The role of opioids and opioid medications in ADHD symptoms is still largely understudied. We tested the hypothesis that, in Heroin Use Disorder (HUD), when patients are treated with Agonist Opioid medications (AOT), treatment outcome is associated with the presence of Adult Attention-Deficit/Hyperactive Disorder (A-ADHD) symptomatology. A retrospective cohort study of 130 HUD patients in Castelfranco Veneto, Italy, covering 30 years, was divided into two groups according to the Adult ADHD Self-Report Scale (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 75 publications
(83 reference statements)
0
13
0
Order By: Relevance
“…This scoping review identified 18 studies (Figure 1) evaluating important health outcomes among patients with OUD and ADHD within addiction treatment programs. 6,9,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] The sample size of the included studies ranged from 12 to 81 752 patients. 6,9,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] The follow-up period of longitudinal studies ranged from 12 weeks to 30 years.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This scoping review identified 18 studies (Figure 1) evaluating important health outcomes among patients with OUD and ADHD within addiction treatment programs. 6,9,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] The sample size of the included studies ranged from 12 to 81 752 patients. 6,9,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] The follow-up period of longitudinal studies ranged from 12 weeks to 30 years.…”
Section: Resultsmentioning
confidence: 99%
“…6,9,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] The sample size of the included studies ranged from 12 to 81 752 patients. 6,9,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] The follow-up period of longitudinal studies ranged from 12 weeks to 30 years. [24][25][26][27][28][29][30][31][32][33][34]38,39 Included in this review were 1 placebo-controlled trial, 24 5 prospective observational studies, 25,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations